2006
DOI: 10.1557/proc-0955-i07-37
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Polarity Control of GaN and AlN on Carbon-face SiC by Metalorganic Vapor Phase Epitaxy

Abstract: Growth and polarity control of GaN and AlN on carbon-face SiC (C-SiC) by metalorganic vapor phase epitaxy (MOVPE) are reported. The polarities of GaN and AlN layers were found to be strongly dependent on the pre-growth treatment of C-SiC substrates. A pre-flow of trimethyaluminum (TMAl) or a very low NH3/TMAl ratio results in Al(Ga)-polarity layers on C-SiC. Otherwise, N-polarity layers resulted. The polarities of AlN and GaN layers were conveniently determined by their etching rate in KOH or H3PO4, a method r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Previously, it was reported that a pre-flow of metal precursors (e.g. trimethylaluminum (TMAl), Al(CH 3 ) 3 , trimethylgallium (TMGa), Ga(CH 3 ) 3 ) or a low V/III (NH 3 /TMAl)-ratio flow [68,71] would result in metal-polarity layers on carbon-face (C-face) SiC substrates instead of expected N-polar layers. Polarity inversion from metal-polar to N-polar or mixed polarity could be triggered by e.g., substrate treatment or deposition of a low-temperature buffer layer [72].…”
Section: History and Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was reported that a pre-flow of metal precursors (e.g. trimethylaluminum (TMAl), Al(CH 3 ) 3 , trimethylgallium (TMGa), Ga(CH 3 ) 3 ) or a low V/III (NH 3 /TMAl)-ratio flow [68,71] would result in metal-polarity layers on carbon-face (C-face) SiC substrates instead of expected N-polar layers. Polarity inversion from metal-polar to N-polar or mixed polarity could be triggered by e.g., substrate treatment or deposition of a low-temperature buffer layer [72].…”
Section: History and Challengesmentioning
confidence: 99%
“…Another major challenge of N-polar III-nitride epitaxy is polarity inversion. It was reported that the polarities of GaN and AlN layers were highly dependent on the pretreatment of C-face SiC substrates [71]. A pre-flow of TMAl on the surface of C-face SiC substrate before AlN nucleation layer growth, or a very low NH 3 /TMAl ratio at the initial growth stage of AlN result results in inversion to aluminum-polar (Al-polar) AlN or Ga-polar GaN.…”
Section: Mocvd Of N-polar Aln and Gan Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Nitrogen-rich growth conditions with a high V/III ratio were claimed to be required to realize N-polar III-nitride layers. 18,19 Furthermore, a distinct unintentional impurity incorporation of oxygen, carbon, and hydrogen in N-polar GaN layers was reported. 22 In our recent study, a three-dimensional (3D) growth mode of N-polar AlN NLs on SiC (0001̅ ) was identified as the likely cause for the observed polarity inversion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, for metal− organic chemical vapor deposition (MOCVD) growth on Cface SiC substrates, where AlN nucleation layers (NLs) were deposited using a low V/III ratio, spontaneous polarity inversion was observed in N-polar AlN and GaN layers. 18,19 The preflow of trimethylaluminum (TMAl) for surface treatment of C-face SiC substrates was found to result in metal-polar instead of N-polar material. 20 Nitrogen-rich growth conditions with a high V/III ratio were claimed to be required to realize N-polar III-nitride layers.…”
Section: ■ Introductionmentioning
confidence: 99%